The law of non-international armed conflict - Sivakumaran, Sandesh (Oxford, U.K. : Oxford University Press, 2012)
"This book brings together and critically analyzes the disparate conventional, customary, and soft law relating to non-international armed conflict. All the relevant bodies of international law are considered, including international humanitarian law, international criminal law, and international human rights law. The book traces the changes to the legal framework applicable to non-international armed conflict from ad hoc regulation in the nineteenth and early twentieth century, to systematic regulation through the 1949 Geneva Conventions and 1977 Additional Protocols, to the transformation of the law in the mid-1990s. Armed conflicts ranging from the US civil war, the Algerian War of Independence, and the attempted secession of Biafra, through to the current conflicts in the Colombia, Philippines, and Sudan are all considered. The identification and analysis of the law is complemented by a consideration of the practice, allowing both violations of, and respect for, the law, to be ascertained. Given that non-international armed conflicts are fought between states and non-state armed groups, or between armed groups, particular attention is paid to the oft-neglected views of armed groups. This is done through an analysis of hundreds of statements, unilateral declarations, internal regulations, and bilateral agreements issued by armed groups. Equivalent material emanating from states parties to conflicts is also considered. The book is thus an essential reference point for the law and practice of non-international armed conflicts"--Provided by publisher.
pt. I. Regulating non-international armed conflicts -- Ad-hoc regulation -- Systematic regulation through international humanitarian law -- Regulation through a body of international law -- The sources of the law of non-international armed conflict -- pt. II. The substantive law of non-international armed conflict -- Identifying a non-international armed conflict : armed conflicts and internal tensions and disturbances -- Identifying a non-international armed conflict : international and non-international armed conflicts -- Scope of application -- Protection of civilians and persons hors de combat -- Conduct of hostilities -- Implementation and non-judicial enforcement -- Judicial enforcement -- pt. III. Moving forward -- Developments needed in the law.
Includes bibliographical references (pages 571-618) and index.
Keywords: Civil war; War (International law)